Physical Quality of Fresh Cayenne Pepper (Capsicum frutescens L.) with Different Types of Packaging during Low Temperature Storage - Dian Purbasari; Erieztine Fitriya Sari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Cayenne pepper (Capsicum frutescens L.) is classified as a horticulture product that easly damaged and it can only survive for 2-3 days in room temperature conditions. In maintaining the quality and self life time of fresh cayenne pepper during storage it is recommended to use the packaging and storage at low temperature. The purpose of this study is to analize the effect of packaging type and storage length on the physical quality of fresh cayenne pepper during low temperature storage (5°C). This study used a complete randomized design method with two factors, each of which consisted of 3 levels, namely storage time (4, 8, and 12 days) and type of packaging (vacuum pack, perforated polypropyline plastic, and wrap plastic). The data were analized by using factorial Anova two mix factors test (α= 5%) and was followed up by Tukey test. The results showed that the best packaging was found in perforated polypropylene plastic with the lowest moisture content 76.45%, the lowest weight loss 3.87%, the highest texture (hardness) 0.027 N/mm², the highest lightness (L*) 44.52, the lowest redness (a*) 26.7, the lowest yellowness (b*) 10.97, the lowest ΔE 23.47, and the lowest water activity 0.889. Physical quality of fresh cayenne pepper can last up to 12 days at low temperature storage (5°C) using perforated polypropylene plastic. Keywords:  Cayenne pepper, packaging, storage, low temperature, physical quality.